Phytochemical Screening and Toxicity Testing of Red Turmeric (Curcuma zedoaria) and White Turmeric (Curcuma mangga) Extracts in White Wistar Rats (Rattus norvegicus) - Rita Kirana; Agus Rachmadi; Nurlailah (Postgraduate, University of Mataram, 2026)
This study aimed to conduct phytochemical analysis and toxicity testing of Red Turmeric (Curcuma zedoaria) and White Turmeric (Curcuma mangga) extracts in male Wistar rats (Rattus norvegicus). This study employs an experimental design conducted at the Poltekkes Kemenkes Banjarmasin laboratory. Phytochemical screening was undertaken to detect bioactive compounds utilizing spectrophotometry for quantitative analysis, with each compound evaluated in triplicate. The experimental subjects were male Wistar rats, divided into two treatment groups (300 mg/kgBW and 2000 mg/kgBW), with observations recorded at multiple intervals (30 minutes to 14 days) post-administration. Toxicity indicators included physical symptoms such as skin conditions, lethargy, and survival status. Data were analyzed descriptively, calculating the mean and standard deviation for phytochemical content and employing frequency tables to highlight clinical symptom patterns. Results showed that both types of turmeric contain these compounds, with White Turmeric having higher phenolic (23.41 mg/g) and flavonoid (17.21 mg/g) contents than Red Turmeric (21.72 mg/g and 15.50 mg/g, respectively). These findings indicate a higher antioxidant potential in White Turmeric. In the toxicity test, two doses (300 mg/kgBW and 2000 mg/kgBW) were tested through observations of physical conditions, including skin and fur, as well as clinical symptoms such as lethargy, seizures, tremors, diarrhea, and survival status.